Securities Property In The Philippines: A State Common Law Imbroglio - Ong, -; Spink, PM (Journal of Malaysian and Comparative Law, 2002)
At the beginning of the twentieth century the commercial law of the Philippines, which had come to embody a synthesis of the Spanish civil law and United States (hereafter 'US') common law, was heralded as one of the most modern and progressive sysytems of law in the Asian region. One example of the early infusion of US common law can be found in the field of law governing security over personal property, where new security instruments were introduced by the then US Administration of the Philippines. This measure was deemed necessary in order to promote the economic design of the Administration, which was to transform the essentially agrarian economy of the Philippines into a vibrant and expansive commercial economy of free and smoothly flowing capital and trade.